Zinc oxide nanowire-collagen composite casing and preparation method thereof
By compounding zinc oxide nanowires with collagen, casings with high mechanical properties, antibacterial properties and barrier properties are prepared, which solves the problem of insufficient performance of existing collagen casings in these aspects and reduces costs.
Patent Information
- Application Number
- CN202411325967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing collagen casings have not yet met the needs of modern society in terms of mechanical strength and antibacterial properties, and casings made of sheepskin are costly.
Zinc oxide nanowires are used to complex with collagen, and zinc oxide nanowires are added to the sheepskin, and zinc oxide nanowires are prepared through acidification, crushing, mixing and wind-pressing blowing.
The mechanical properties, antibacterial properties and barrier properties of the casing are improved, and the loss of leather during the preparation process is reduced, and the cost is relatively low.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of collagen membranes, and particularly relates to a zinc oxide nanowire-collagen composite sausage casing and a preparation method thereof. Background Art
[0002] In the meat processing industry, casings play a vital role. They are a key component in making sausages and other sausage products, and help maintain the quality of the product over a certain period of time. Traditionally, the production of meat products relies on natural animal casings, but the limited supply and varying sizes of this material limit its application in production. Collagen is valued for its excellent film-forming ability. It can not only be used in the medical field as a medical membrane material such as artificial skin, but also as a food packaging film. It is widely used in various foods such as meat products, smoked foods, fried foods, yogurt, and food ingredients. Although collagen extracted from cowhide can form a complete helical structure, the collagen film and composite film made from it have not yet reached the standards required for casings in terms of mechanical strength and flexibility. At present, the use of collagen alone as a material can no longer meet the modern society's demand for material versatility and high strength.
[0003] Most collagen casings sold on the market are made from cowhide, although there are also products using other animal hides such as pigskin and sheepskin. Cowhide has become the mainstream choice due to its easy access, abundant production and low cost. However, collagen casings made from cowhide often have coarser fibers, and when large-sized casings are produced, their toughness is insufficient, which can easily lead to casing rupture, thus affecting their practicality. On the other hand, collagen films made from sheepskin have better toughness, but due to the low production and high price of sheepskin, if sheepskin is used entirely to produce collagen casings, the cost will be relatively high.
[0004] With the development of nanotechnology, the development and application of nanomaterials have received more and more attention and research. Nano zinc oxide has the advantages of high biosafety and good antibacterial properties, providing a new direction for improving the performance of collagen fiber membranes. In the field of food packaging, nano zinc oxide is added to composite films to enhance their mechanical strength and antibacterial effects. Nano zinc oxide can improve the gel strength of composite films and significantly improve the antibacterial effect at a certain concentration. In addition, the introduction of zinc oxide can also improve the impedance performance of composite films and reduce water vapor permeability and water solubility. Summary of the invention
[0005] Through research, it was found that zinc oxide can be used as a nutritional enhancer and antibacterial agent in the production of casings. As a nutritional enhancer, zinc oxide can supplement the zinc element in casings, which plays an important role in human growth and development, immune function, skin health, etc. As an antibacterial agent, zinc oxide can inhibit the growth and reproduction of various bacteria and improve the hygienic safety of casings. In addition, zinc oxide also has an antioxidant effect, which can protect the nutrients in the casings from oxidation and extend the shelf life of the casings. However, at present, in the production of casings, there are no reports that zinc oxide may be used as an auxiliary material to improve the performance of casings or as an additive in the production process. Therefore, how to provide a method for enhancing the mechanical properties and antibacterial properties of collagen casings with nano zinc oxide is a problem that technicians in this field urgently need to solve.
[0006] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0007] The present invention provides a method for preparing a zinc oxide nanowire-collagen composite casing, comprising the following steps:
[0008] S1: Add lime, liming aid and water to the sheepskin, make the sheepskin evenly coated with lime, and place at 10-30℃ for 12-24h;
[0009] S2: acidifying the sheepskin after being placed in step S1 to obtain acidified sheepskin;
[0010] S3: impact-crushing the acidified skin, mixing evenly, adding into water and zinc oxide nanowires, and mixing to obtain a collagen solution;
[0011] S4: adjusting the pH of the collagen solution to 6-7 to aggregate the collagen to form collagen clusters;
[0012] S5: taking out the collagen mass and dehydrating it;
[0013] S6: The collagen mass dehydrated in step S5 is blown by wind pressure technology to obtain a zinc oxide nanowire-collagen composite casing.
[0014] Preferably, in step S1, the amount of lime used is 7-15% of the mass of the sheepskin.
[0015] Preferably, in step S1, the amount of the liming auxiliary agent used is 2-8% of the mass of the sheepskin.
[0016] Preferably, in step S1, the amount of water used is 40-80% of the mass of the sheepskin.
[0017] Preferably, in step S1, the liming aid is a mixture of alkaline protease and ammonium salt; the mass ratio of the alkaline protease to the ammonium salt is 1-3:7-10.
[0018] Preferably, in step S2, the pH of the acidification is 3.4-4.2, and the acidification time is 18-36 hours.
[0019] Preferably, in step S2, the mass ratio of the acidified skin, zinc oxide nanowires and water is 1-2:1:10-14.
[0020] Preferably, in step S2, the zinc oxide nanowires are prepared by a hydrothermal method, an electrochemical method or a sol-gel method.
[0021] Preferably, in step S2, the zinc oxide nanowires are obtained by heating a zinc salt at 80-100° C. for reaction, adding an aluminum oxide template for evaporation, and then annealing.
[0022] Preferably, in step S5, the moisture content is controlled to be between 85% and 95% during dehydration.
[0023] The present invention also provides a zinc oxide nanowire-collagen composite casing prepared by the above preparation method.
[0024] The technical solution of the present invention has the following advantages over the prior art:
[0025] The invention discloses a zinc oxide nanowire-collagen composite sausage casing and a preparation method thereof. By utilizing the advantages of zinc oxide nanowires that can be used as a nutritional enhancer and an antibacterial agent, a sausage casing with the advantages of being resistant to cooking, having strong antibacterial properties, and having good mechanical properties and barrier properties is prepared.
[0026] (1) The present invention further improves the quality of the casing by using a reinforcing material (nano zinc oxide) while maintaining the inherent taste, shrinkage rate, and adhesion to meat of the casing, thereby reducing the loss of skin material during the preparation process and improving the mechanical properties of the casing.
[0027] (2) The present invention utilizes zinc oxide nanomaterials to generate reactive oxygen species (ROS) which in turn causes bacterial death, thereby improving the antibacterial properties of the collagen casing and increasing the shelf life of the casing. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0029] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0030] The ammonium salt is ammonium chloride, and the enzymatic liming aid alkaline protease NOWOLASE XL is purchased from Shanghai Shenggong.
[0031] Example 1
[0032] A method for preparing a composite collagen casing comprises the following steps:
[0033] (1) adding lime (7% of the mass of the sheepskin), a liming aid (a mixture of alkaline protease and ammonium salt, with a mass ratio of (1):(7), and an amount of 2%), and water (40% of the mass of the sheepskin) to the sheepskin, allowing the sheepskin to be evenly coated with lime, and placing it at 10 degrees Celsius for 24 hours;
[0034] (2) Wash off the lime on the surface of the leather and acidify the leather to pH 3.8 for 22 hours;
[0035] (3) Preparation of zinc oxide nanowires by sol-gel method; for specific methods, refer to Yu Mei, Liu Jianhua, Li Songmei, et al. Preparation and characterization of zinc oxide nanowire / tube arrays by sol-gel template method [J]. Journal of Inorganic Materials, 2005, 20(6): 1363-1367. DOI: 10.3321 / j.issn:1000-324X.2005.06.015. Weigh 2 g of citric acid, dissolve it in 20 ml of water, and heat it until it is completely dissolved to obtain liquid A. Then weigh 11.9 g of zinc nitrate, dissolve it in 10 ml of water, and then transfer the zinc nitrate solution to liquid A. Under magnetic stirring, maintain the reaction at 80 degrees Celsius for 1 hour. Then, heat it to boiling, and when the volume of the solution is reduced to 10 ml, add the aluminum oxide template and continue boiling and evaporation until the water is completely evaporated to form a wet gel. Then remove the template and wipe off the excess gel. After standing at room temperature (25°C) for half an hour, the dried gel was transferred to a muffle furnace for annealing (500°C for 1 hour). After annealing, the gel was cooled to room temperature in the furnace.
[0036] (4) crushing the acidified sheepskin by impact and mixing, pouring into deionized water, adding zinc oxide nanowires, the mass ratio of the acidified sheepskin, zinc oxide nanowires, and deionized water being (1):1:(10), stirring until there is no solid in the solution to obtain a collagen solution, adjusting the pH of the collagen solution to 6.5, so that the collagen aggregates to form collagen clusters;
[0037] (5) Remove the collagen mass and dehydrate it to control the water content at 85%;
[0038] (6) Blowing the collagen mass into casing using air pressure technology.
[0039] Example 2
[0040] A method for preparing a composite collagen casing comprises the following steps:
[0041] (1) adding lime (10% of the mass of the sheepskin), a liming aid (a mixture of alkaline protease and ammonium salt, with a mass ratio of (1):(10), and an amount of 5%), and water (40% of the mass of the sheepskin) to the sheepskin, allowing the sheepskin to be evenly coated with lime, and placing it at 20 degrees Celsius for 16 hours;
[0042] (2) Wash off the lime on the surface of the leather, acidify the leather to pH 8, and acidify for 18 hours;
[0043] (3) Prepare zinc oxide nanowires by sol-gel method; weigh 2 g of citric acid, dissolve it in 20 ml of water, and heat until completely dissolved, liquid A. Then weigh 11.9 g of zinc nitrate, dissolve it in 10 ml of water, and then transfer the zinc nitrate solution to liquid A. Under magnetic stirring, maintain the reaction at 80 degrees Celsius for 1 hour. Then, heat to boiling, and when the volume of the solution is reduced to 10 ml, add the alumina template and continue boiling and evaporation until the water is completely evaporated to form a wet gel. Then remove the template and wipe off the excess gel. Let it stand at room temperature for half an hour, then transfer the dried gel to a muffle furnace for annealing (500 degrees Celsius for 1 hour). After annealing, cool to room temperature with the furnace.
[0044] (4) crushing the acidified sheepskin by impact and mixing, pouring into deionized water, adding zinc oxide nanowires, the mass ratio of the acidified sheepskin, zinc oxide nanowires, and deionized water being (1):1:(10), stirring until there is no solid in the solution to obtain a collagen solution, adjusting the pH of the collagen solution to 6.5, so that the collagen aggregates to form collagen clusters;
[0045] (5) Remove the collagen mass and dehydrate it to control the water content at 90%;
[0046] (6) Blowing the collagen mass into casing using air pressure technology.
[0047] Example 3
[0048] A method for preparing a composite collagen casing comprises the following steps:
[0049] (1) adding lime (15% of the mass of the sheepskin), a liming aid (a mixture of alkaline protease and ammonium salt, with a mass ratio of (1):(10), and an amount of 2%), and water (80% of the mass of the sheepskin) to the sheepskin, allowing the sheepskin to be evenly coated with lime, and placing it at 20 degrees Celsius for 12 hours;
[0050] (2) Wash off the lime on the surface of the leather and acidify the leather to pH 4.2 for 24 hours;
[0051] (3) Prepare zinc oxide nanowires by sol-gel method; weigh 2 g of citric acid, dissolve it in 20 ml of water, and heat until completely dissolved, liquid A. Then weigh 11.9 g of zinc nitrate, dissolve it in 10 ml of water, and then transfer the zinc nitrate solution to liquid A. Under magnetic stirring, maintain the reaction at 80 degrees Celsius for 1 hour. Then, heat to boiling, and when the volume of the solution is reduced to 10 ml, add the alumina template and continue boiling and evaporation until the water is completely evaporated to form a wet gel. Then remove the template and wipe off the excess gel. Let it stand at room temperature for half an hour, then transfer the dried gel to a muffle furnace for annealing (500 degrees Celsius for 1 hour). After annealing, cool to room temperature with the furnace.
[0052] (4) crushing the acidified sheepskin by impact and mixing, pouring into deionized water, adding zinc oxide nanowires, the mass ratio of the acidified sheepskin, zinc oxide nanowires, and deionized water being (1):1:(10), stirring until there is no solid in the solution to obtain a collagen solution, adjusting the pH of the collagen solution to 7, so that the collagen aggregates to form collagen clusters;
[0053] (5) Remove the collagen mass and dehydrate it to control the water content at 95%;
[0054] (6) Blowing the collagen mass into casing using air pressure technology.
[0055] Comparative Example 1
[0056] A method for preparing a composite collagen casing comprises the following steps:
[0057] The difference between this comparative example and Example 1 is that the nano zinc oxide is replaced with hydroxypropyl methylcellulose.
[0058] (1) adding lime (7% of the mass of the sheepskin), a liming aid (a mixture of alkaline protease and ammonium salt, with a mass ratio of (1):(7), and an amount of 2%), and water (40% of the mass of the sheepskin) to the sheepskin, allowing the sheepskin to be evenly coated with lime, and placing it at 30 degrees Celsius for 12 hours;
[0059] (2) Wash off the lime on the surface of the leather and acidify the leather to pH 4.2 for 24 hours;
[0060] (3) crushing the acidified sheepskin by impact and mixing, pouring into deionized water, adding hydroxypropyl methylcellulose, the mass ratio of the acidified sheepskin, hydroxypropyl methylcellulose, and deionized water being (1):1:(10), stirring until there is no solid in the solution to obtain a collagen solution, adjusting the pH of the collagen solution to 7, so that the collagen aggregates to form collagen clusters;
[0061] (4) Remove the collagen mass and dehydrate it to control the water content at 85%;
[0062] (5) Blowing the collagen mass into casing using air pressure technology.
[0063] Effect evaluation 1
[0064] The tensile strength and elongation at break of the above-mentioned embodiments and comparative examples were measured according to SB / T 10373-2012. After being prepared into sausages, the taste was tasted and the skin-meat bonding test results were shown in Table 1:
[0065] Table 1 Performance characterization of nano zinc oxide reinforced collagen casing
[0066] Mean tensile strength Mean elongation at break Taste Skin and flesh Comparative Example 1 6.6N 43% Slight chewy feeling Good skin-flesh combination Example 1 10.6N 63% Slight chewy feeling Good skin-flesh combination Example 2 11.1N 57% Slight chewy feeling Good skin-flesh combination Example 3 9.9N 56.2% Slight chewy feeling Good skin-flesh combination
[0067] Table 2 shows the batch numbers, which means that three batches of production tests were conducted.
[0068] Table 2 Application test results
[0069] batch High-speed filling Filling Steaming 1 normal normal normal 2 normal normal normal 3 normal normal normal
[0070] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a zinc oxide nanowire-collagen composite casing, characterized in that: The steps include: S1: Add lime, liming aid and water to the sheepskin, make the sheepskin evenly coated with lime, and place at 10-30℃ for 12-24h; S2: acidifying the sheepskin after being placed in step S1 to obtain acidified sheepskin; S3: impact-crushing the acidified skin, mixing evenly, adding into water and zinc oxide nanowires, and mixing to obtain a collagen solution; S4: adjusting the pH of the collagen solution to 6-7 to aggregate the collagen to form collagen clusters; S5: taking out the collagen mass and dehydrating it; S6: Blowing the collagen mass dehydrated in the step S5 by wind pressure technology to obtain the zinc oxide nanowire-collagen composite casing.
2. The preparation method according to claim 1, characterized in that In the step S1, the amount of lime used is 7-15% of the mass of the sheepskin.
3. The preparation method according to claim 1, characterized in that: In the step S1, the amount of the liming auxiliary agent used is 2-8% of the mass of the sheepskin.
4. The preparation method according to claim 1, characterized in that: In step S1, the amount of water used is 40-80% of the weight of the sheepskin.
5. The preparation method according to claim 1, characterized in that: In the step S1, the liming aid is a mixture of alkaline protease and ammonium salt; the mass ratio of the alkaline protease to the ammonium salt is 1-3:7-10.
6. The preparation method according to claim 1, characterized in that: In step S2, the acidified pH is 3.4-4.2, and the acidification time is 18-36 hours.
7. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the acidified skin, the zinc oxide nanowires and water is 1-2:1:10-14.
8. The preparation method according to claim 1, characterized in that: In the step S2, the zinc oxide nanowires are prepared by a hydrothermal method, an electrochemical method or a sol-gel method.
9. The preparation method according to claim 1, characterized in that: In the step S5, the moisture content is controlled to be between 85% and 95% during dehydration.
10. A zinc oxide nanowire-collagen composite sausage casing prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Antibacterial composite preservative film and preparation method thereof
CN103254650A
Method for preparing gelatin-ZnO nano composite film from tuna heads
CN104877155A
Preparation method of composite collagen casing
CN116138294A
Collagen casings with added chitosan
US20180325128A1